2021
DOI: 10.1128/mcb.00149-21
|View full text |Cite
|
Sign up to set email alerts
|

Erf Affects Commitment and Differentiation of Osteoprogenitor Cells in Cranial Sutures via the Retinoic Acid Pathway

Abstract: ETS2 repressor factor (ERF) haploinsufficiency causes late onset craniosynostosis (OMIM 600775; CRS4) in humans while in mice Erf-insufficiency also leads to a similar multi-suture synostosis phenotype preceded by mildly reduced calvarium ossification. However, neither the cell types affected nor the effects per se have been identified so far. Here we establish an ex vivo system for the expansion of suture-derived mesenchymal stem and progenitor cells (sdMSCs) and analyze the role of Erf levels in their differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 92 publications
2
8
0
Order By: Relevance
“…Although the PF suture in Erf loxP/+ mice at this stage was still well-detected, it displayed closures and deformities in the majority of Erf loxP/− mice. Interrogation of single-cell RNA sequencing data from coronal [24] and frontal [25] sutures for the correlation of Erf expression with other genes, as previously described [22], indicated the mediation of additional pathways in the frontal suture, notably involving signaling and motility (Supplementary Figure S1). To evaluate possible qualitative differences in the ossification of cranial sutures, we utilized Raman spectroscopy on mouse calvaria at P65.…”
Section: Erf Insufficiency In Mice Is Associated With Both Craniosyno...supporting
confidence: 59%
See 1 more Smart Citation
“…Although the PF suture in Erf loxP/+ mice at this stage was still well-detected, it displayed closures and deformities in the majority of Erf loxP/− mice. Interrogation of single-cell RNA sequencing data from coronal [24] and frontal [25] sutures for the correlation of Erf expression with other genes, as previously described [22], indicated the mediation of additional pathways in the frontal suture, notably involving signaling and motility (Supplementary Figure S1). To evaluate possible qualitative differences in the ossification of cranial sutures, we utilized Raman spectroscopy on mouse calvaria at P65.…”
Section: Erf Insufficiency In Mice Is Associated With Both Craniosyno...supporting
confidence: 59%
“…In contrast, its absence can affect the differentiation of multiple cell types and can cause malignant transformation [16][17][18][19][20][21]. Recently, we showed that Erf is required for the efficient commitment of suture-derived mesenchymal stem/progenitor cells toward the osteogenic lineage via the retinoic acid (RA) pathway [22]. As RA acts as a morphogen and is reported to have a role in bone development, precise control of ERF nuclear levels and transcriptional effects appear to be important for multiple cellular fates.…”
Section: Introductionmentioning
confidence: 99%
“…59 Recently, Erf was shown to affect the osteogenic differentiation of cranial suture mesenchymal stem/progenitor cells through retinoic acid (RA) pathway regulation. 60 as these genes contain Ets binding sites 63,64 and Erf might act as transactivator in some settings, as suggested by the down-regulation of genes with Erf chromatin binding after Erf deactivation. 65 ThPOK has not been reported as an ETS transcription target.…”
Section: Discussionmentioning
confidence: 99%
“…Direct transcriptional regulation would also be possible in response to fluctuation in Erk activity, observed during thymocyte maturation 59 . Recently, Erf was shown to affect the osteogenic differentiation of cranial suture mesenchymal stem/progenitor cells through retinoic acid (RA) pathway regulation 60 . RA receptor transcriptional activity was previously shown to increase in DP thymocytes and in SP cells during lineage commitment, 61 whereas the addition of RA in murine fetal thymic organ cultures was shown to drive an increase in CD4 + SP thymocytes, 62 indicating a role of RA pathway in the regulation of T cell maturation.…”
Section: Discussionmentioning
confidence: 99%
“…5c). For example, Module 3 consisted hypertrophic chondrocytes and chondrocytes cluster, containing common regulons of ERF 49 , FOXC1 50 and ATF2 51 which were reported to participate in the bone formation and osteogenic differentiation. Module 10 was composed of hypertrophic chondrocytes and osteoblasts, containing common regulons of SOX8 52 and ESRRA 53 which were essential regulators for chondrogenic and osteoblast differentiation (Fig.…”
Section: Discussionmentioning
confidence: 99%